2002
DOI: 10.1046/j.1365-2648.2002.02091.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of sex‐role stereotypes, self‐concept, and nursing role ideal in Chinese nursing students

Abstract: The conclusions highlight implications for the recruitment and education of both male and female nursing students in Hong Kong society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
2
16
0
1
Order By: Relevance
“…The sociodemographic data obtained indicate that this activity continues to be a mainly female area (Cash, 1997;Davis, 1995;Holroyd et al, 2002;Meadus, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…The sociodemographic data obtained indicate that this activity continues to be a mainly female area (Cash, 1997;Davis, 1995;Holroyd et al, 2002;Meadus, 2000).…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Research does suggest that particular personalities are associated with particular occupations (Clow & Esses, 2005; Holroyd, Bond, & Chan, 2002). More importantly, Hoffman and Hurst (1990) used fictional groups of individuals to experimentally demonstrate that stereotypes could develop solely from the distribution of groups of people into particular social roles—even when the personalities of those individuals did not actually differ.…”
Section: Three Theories Pertaining To Gender Inequalitymentioning
confidence: 99%
“…As nurses currently tend to be women worldwide, this gendered division of labor in health care may encourage the development of stereotypes suggesting that there is something inherent in a woman that is necessary for being a nurse (see Clow and Ricciardelli 2011). In Hong Kong, male and female nursing students rated the typical Chinese nurse as very similar to the typical female in Chinese society (Holroyd et al 2002). In Ireland, Loughrey (2008) found that more male nurses identified with the female gender role than the male gender role and he suggested that "adherence to the female gender role may be an important prerequisite to caring" (p. 1327).…”
Section: Introductionmentioning
confidence: 99%